(untitled) (TECHNICAL SCIENCE RESEARCH IN UZBEKISTAN, 2024)
The equations of kinetostatics are compiled and the reaction forces of constraints of a non-axisymmetric (triangular) wedge are determined according to the d’Alembert principle. A mathematical expression is obtained for the reaction force of the kinetostatics problem of a non-axisymmetric wedge under the action of a non-constant force. The research methods are based on the classical methods of theoretical mechanics of deriving the equation of dynamics based on the d’Alembert principle and the analytical method for determining the reaction force of constraints.